PERANAN MAHASISWA KKN DALAM PENYULUHAN DAN SOSIALISASI PROKES COVID-19 DI LINGKUNGAN PONDOK PESANTREN DARUL FALAH - Komarudin Komarudin (Jurnal Al Maesarah, 2022)
Covid-19 pandemic is a problem in the health sector that has a domino effect in the education sector. Not only changes in primary, secondary, and higher education, even in higher education, education personnel are very much felt. Starting from the education and research system, especially in community service. STAI Darul Falah through the Institute for Research and Community Service (LPPM) formulated the Standard Operational Procedure (SOP) for the Covid-19 Pandemic Emergency in the field of community service for students and lecturers. miniature of the existing society. One of the students from group 21 chose to carry out community service at the Darul Falah Islamic boarding school with the target of counseling on the COVID-19 prokes and learning assistance. The interview, documentation and observation methods were chosen because they are considered to be very effective and efficient in this study which includes the population and the sample is KKN students and Darul Falah Islamic Boarding School Santri. The results of the research on the role of real work lectures at the Darul Falah Islamic boarding school were very beneficial for the boarding school residents, both asatidz and murobbi who were helped in socializing and counseling the importance of implementing health programs for pesantren residents and of course for students the benefit was that they could still carry out the tridarma of higher education services. the community well in the midst of the covid-19 pandemic.